Penggunaan Denda Damai oleh Kejaksaan Sebagai Alternatif dalam Penyelesaian Tindak Pidana Ekonomi - Bagas Satria Wicaksono (SAKINAH: Jurnal Hukum Keluarga Islam, 2024)
Abstract: This research aims to understand the meaning of peace fines as regulated in article 35 paragraph (1) letter k of the Prosecutor's Law, understand the mechanism for using peace fines by prosecutors for economic crimes in the analysis of legal certainty, and understand how peace fines are ideally regulated. by the prosecutor's office in handling economic crimes in the future. The research method used is normatif juridical using 3 legal approaches, including: Legislative Approach, Conceptual Approach, Case Approach. From the research results, it is clear that the meaning of a peace fine can be interpreted as stopping the prosecution of a case involving an economic crime with the payment of a fine agreed upon by the Attorney General and the perpetrator. The procedural law for peace fines in non-economic crimes is based on the principles of prosecution, and in the procedural law the use of peace fines itself must fulfill things such as subject, object, delegation of authority, methods and conditions for the use of peace fines. Then, in the mechanism for using peaceful fines that will later be implemented, it is mandatory to pay attention to several principles in prosecution procedures so that they can provide three legal values ​​(justice, certainty and benefit) to the community. Keywords: Peace Fines, Attorney General, Economic Crimes   Abstrak: Penelitian ini bertujuan untuk memahami makna dari denda damai sebagaimana diatur dalam pasal 35 ayat (1) huruf k Undang-undang Kejaksaan, untuk memahami bagaimana mekanisme penggunaan denda damai oleh kejaksaan pada tindak pidana ekonomi dalam analisis kepastian hukum, dan untuk memahami bagaimana pengaturan denda damai secara ideal oleh kejaksaan dalam menangani tindak pidana ekonomi pada masa mendatang. Metode penelitian yang digunakan yaitu yuridis normatif menggunakan 3 pendekatan hukum antara lain: Pendekatan Perundang-undangan, Pendekatan Konseptual, Pendekatan Kasus. Dalam hasil penelitian ini secara jelas makna denda damai dapat diartikan sebagai penghentian penuntutan perkara dalam tindak pidana ekonomi dengan pembayaran denda yang disetujui oleh Jaksa Agung dan pelaku. Adapun hukum acara denda damai dalam tidak pidana ekonomi didasari dengan adanya asas-asas dalam penuntutan, serta dalam hukum acara penggunaan denda damai sendiri harus memenuhi hal-hal seperti subjek, objek, pendelegasian wewenang, metode, dan syarat penggunaan denda damai. Kemudian pada mekanisme penggunaan denda damai yang nantinya akan diterapkan wajib mematuhi beberapa asas-asas dalam prosedur penuntutan sehingga dapat memberikan tiga nilai hukum (keadilan, kepastian, dan kemanfaatan) pada masyarakat. Kata Kunci: Denda Damai, Jaksa Agung, Tindak Pidana Ekonomi